Photolability of per-arylated butadienes: en route to dihydronaphthalenes - Freudenberg, Jan; Uptmoor, Andrea Christina; Rominger, Frank; Bunz, Uwe H. F. (The journal of organic chemistry, 2014)
Arylated butadienes were prepared employing transition-metal coupling techniques and characterized via UV/vis spectroscopy and X-ray crystal structure analysis. Identification of byproducts led to a photochemical route toward novel multiarylated dihydronaphthalenes. Arylbutadiene-dihydronaphthalene cyclization occurs in solution and in the solid state. Upon substitution of hexaphenylbutadiene, absorption is red-shifted and stability under ambient light is even more reduced.
Gesehen am 19.10.2020